Ford's Gamma‐Gamma Village Simulation Revisited: Highlighting the Need for a New Middle‐Range Theory of Archaeological Types. (9th March 2021) - MacLeod, N.; Nash, B.
Abstract : The long‐running controversy over typological concept use in archaeological investigations hinges on whether such procedures introduce assumptions, and channel interpretations, in ways that can equate analytical groups with bounded cultural‐historical units inappropriately. James A. Ford ' s writings, in reaction to the arguments of Albert Spaulding, have often been cited as the founding instance of this criticism. To illustrate his concerns, Ford drew a hypothetical village of houses and used these forms to make a number of assertions regarding the nature of artifact variability that, he felt, demonstrated inherent errors with Spaulding ' s artifact‐analysis approach. However, despite the intense character of this controversy, both at the time and subsequently, no one appears to have tested, or confirmed, any of Ford ' s assertions objectively. Morphometric analyses of Ford's simulation demonstrates all published assertions of which we are aware regarding patterns of variation exhibited by these drawn artifact forms, published in the intervening 67 years, are either wholly or substantially incorrect. Both traditional and new pattern‐recognition techniques allow for the identification of more fine‐grained structure in artifact variation patterns than is possible using qualitative approaches. These findings argue strongly for a re‐evaluation of the role of typology in archaeological research.